Engineering an empire the complete series - Weller, Peter, 1947-; Carroll, Michael (Associate professor of literature); Cassel, Chris; Arts and Entertainment Network; History Channel (Television network); Kralyevich Productions; New Video Group ([New York, N.Y.] : History Channel : Distributed by New Video, 2007)
"Circles the globe to re-examine history's most magnificent civilizations by surveying the architectural and engineering triumphs they left behind" -- Container.
disc 1 (132 min.). Greece ; Greece : age of Alexander / produced, written & directed by Ted Poole (44 min. each) ; The Aztecs / produced, written & directed by Jim Gaffey (44 min.) -- disc 2 (132 min.). Carthage / produced, written & directed by Jessica Conway (44 min.) ; China / produced, written & directed by Joanna Chejade-Bloom, Doug Ross (44 min.) ; Russia / produced, written & directed by Sarah Hutt (44 min.) -- disc 3 (133 min.). Britain : blood and steel / produced, written & directed by Kristin Gray (44 min.) ; The Persians / produced, written & directed by Hassan Ildari (45 min.) ; The Maya : death empire / produced, written & directed by Dana K. Ross (44 min.) -- disc 4 (133 min.). Napoleon : steel monster / produced, written & directed by Penny Fearon (45 min.) ; The Byzantines / produced, written & directed by Rebecca J. Ratliff (44 min.) ; Da Vinci's world / produced, written & directed by Anna K. Ross, Gabrielle Mahler (44 min.) -- discs 5 & 6. Rome : engineering an empire ; Egypt : engineering an empire / produced, written & directed by Christopher Cassel ; KPI (91 min. each).
DVD; Dolby digital stereo.
In English.
Host, Peter Weller ; narration, Michael Carroll.
Series director, Mark Cannon ; series producer, Randy Martin.
Collective title from disc labels.
Originally produced as 12 episodes of the television program Engineering an empire in 2006 & 2007 (discs 1-4), and 2 television documentary specials in 2005 ("Rome", disc 5) & 2006 ("Egypt", disc 6).
Keywords: Architecture -- History; Engineering -- History; Documentary television programs